Current status of the Milky Stork Re-introduction Programme in Malaysia and its challenges - Ismail, Ahmad; Abdul Rahman, Mohd Faid (Penerbit Universiti Sains Malaysia, 2016)
This review discussed the current status of the Milky Stork Re-introduction Programme in Malaysia and the challenges it faced. Although it has continued for almost seven years, more challenges appeared as time elapsed mainly due to the arising conflicts between the implementation of conservation policy versus the development projects in Kuala Gula. Hence, the released population is struggling to adapt mainly due to the reduction of suitable habitat for nesting and disturbed foraging areas by the continuous anthropogenic activities. Furthermore, the lack of appropriate training among captive storks prior to being released also slows the adaptation of the birds in their new habitat. The increasing pattern of pollution in the area is also highlighted. Several suggestions were given to help improve the current re-introduction programme. These include improvements to the captive training method, improvement of the existing enclosure’s condition and environment, protection of remaining mangrove forest, creation of a buffer zone to mitigate the increasing pollution level in the area, close monitoring of the released population, and maintaining continuous support and awareness among the public. Considering the ongoing anthropogenic activities that may impair the status of Kuala Gula as an important bird sanctuary, emphasis should be given to achieve sustainable development throughout the area.